Pengaruh Kepemimpinan Transformasional dan Disiplin Kerja terhadap Kinerja Karyawan pada CV. Putra Gemilang Palembang - Amelia, Wijayanti; Roswaty, Roswaty; DP, M. Kurniawan (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to analyze the effect of transformational leadership and work discipline on the employee performance of CV Putra Gemilang Palembang. The data used in this study were primary and secondary data obtained from interviews and questionnaires. The research method used is multiple linear regression analysis. The results indicate that transformational (X1) and work discipline (X2) had a significant positive effect on employee performance (Y). This research is expected to help companies improve employee performance